Dincharya: an Anatomical and Physiological Overview - Sharma, Shaifali; Devpal, Harvendra; Sharma, Dinesh Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is one of the world’s oldest holistic healing system. In Sanskrit, Ayurveda means “The Science of Life.” Ayurveda places great emphasis on prevention and encourages the maintenance of health through close attention to balance in one’s life, right thinking, diet, lifestyle and the use of herbs. Knowledge of Ayurveda enables one to understand how to create this balance of body, mind and consciousness according to one’s own individual constitution and how to make lifestyle changes to bring about and maintain this balance. To maintain the health some activities are mentioned in Ayurveda under the term Dincharya. Here we are going to talk about this Dincharya (daily regimen) as well as its anatomical and physiological effects by following or not following it.